Characterization of psoriasis patients in special body areas: real-world evidence from the Chinese Psoriasis Standardized Diagnosis and Treatment Center - Yuge Gao; Chao Li; Meng Tong; Yizhou Hu; Yuzhen Li (Journal of Dermatological Treatment)
Background While extensive research has provided a wealth of information on psoriasis in general, there remains a critical gap in understanding the unique characteristics of psoriasis in special body areas, such as the scalp, nails, palms, and genitals.Objective To investigate the characterization and treatment of psoriasis patients in special body areas.Methods The study was a retrospective analysis of patients with psoriasis enrolled in the Psoriasis Standardized Diagnosis and Treatment Center Project between January 2020 and September 2021.Results The study encompassed 346 patients, 81% of them had psoriasis in at least two special body areas, with the nails as the most common area. Patients with genital psoriasis reported higher Dermatology Life Quality Index (DLQI) scores. A higher propensity for scalp and palmoplantar psoriasis was noted in patients with genital psoriasis. The proportion of patients treated with biologics rose, as the number of specific areas involved increased.Conclusions Patients with genital psoriasis are more likely to have scalp and palmoplantar psoriasis. This study highlights the significant escalation in the proportion of biologics when the involvement of special body areas was ≥2.